Improved running economy and increased hemoglobin mass in elite runners after extended moderate altitude exposure - Saunders, P. U.; Telford, R. D.; Pyne, D. B.; Gore, C. J. (Journal of Science and Medicine in Sport, 2009)
There is conflicting evidence whether hypoxia improves running economy (RE), maximal O2 uptake (), haemoglobin mass (Hbmass) and performance, and what total accumulated dose is necessary for effective adaptation. The aim of this study was to determine the effect of an extended hypoxic exposure on these physiological and performance measures. Nine elite middle distance runners were randomly assigned to a live high-train low simulated altitude group (ALT) and spent 46 ± 8 nights (mean ± S.D.) at 2860 ± 41 m. A matched control group (CON, n = 9) lived and trained near sea level (600 m). ALT decreased submaximal (L min-1) (-3.2%, 90% confidence intervals, -1.0% to -5.2%, p = 0.02), increased Hbmass (4.9%, 2.3-7.6%, p = 0.01), decreased submaximal heart rate (-3.1%, -1.8% to -4.4%, p = 0.00) and had a trivial increase in (1.5%, -1.6 to 4.8; p = 0.41) compared with CON. There was a trivial correlation between change in Hbmass and change in (r = 0.04, p = 0.93). Hypoxic exposure of 400 h was sufficient to improve Hbmass, a response not observed with shorter exposures. Although total O2 carrying capacity was improved, the mechanism(s) to explain the lack of proportionate increase in were not identified.